Pharmacology of manipulating lean body mass - Sepulveda, Patricio V (Clin Exp Pharmacol Physiol, 2015)
1. Dysfunction and wasting of skeletal muscle as a consequence of illness decreases the length and quality of life. Currently, there are few, if any, effective treatments available to address these conditions. Hence, the existence of this unmet medical need has fuelled large scientific efforts. 2. Fortunately, these efforts have shown many of the underlying mechanisms adversely affecting skeletal muscle health. 3. With increased understanding have come breakthrough disease-specific and broad spectrum interventions, some progressing through clinical development. 4. The present review focuses its attention on the role of the antagonistic process regulating skeletal muscle mass before branching into prospective promising therapeutic targets and interventions. Special attention is given to therapies in development against cancer cachexia and Duchenne muscular dystrophy before closing remarks on design and conceptualization of future therapies are presented to the reader.